The Ambiguities of Retribution*. Issue 6 (3rd July 2017) - Sinclair, Alison
Abstract: The exhibition and shaming through the ordeal of public execution was a way of making public authority's control over wrongdoers. As Michel Foucault has noted, however, this was a process with the unintended potential of arousing admiration or sympathy in the spectator. In Spain the figure of the bandolero, despite crimes sufficient to take him to the gallows, was frequently presented in a positive light. The images in pliegos sueltos which commemorate bandoleros and other popular wrongdoers form part of a historical backcloth in which the bodies of those executed were exposed for the demonstration of the power that had brought them to justice. There are, however, elements in the sueltos which undermine the message of control conveyed by an execution. In the images at least, the most extreme forms of the suffering tend to be suppressed, although the details of crimes may be included with some detail. At the same time the text of the sueltos sometimes includes elements typical of a narrative of heroism that are strongly at odds with the images of wrongdoers brought to heel. Circumstantial details of the criminals may offset their depiction as worthy of condemnation, and—in more active mode—their bragging stands in dramatic tension with a containing text of authority. The whole brings into question the place of the sueltos in a dynamic of state and people, of control and response, of heroism of the person versus submission to the law. Examples discussed include the Vázquez brothers, Diego Corrientes, Juan de Serrallonga, Jaime el Barbudo, Carmelo Ausejo Alacot and Juan Portela.